Video assisted thoracoscopy in thoracic injury: early or delayed indication? - Divisi, D.; Battaglia, C.; De Berardis, et al., B. (Acta Biomedica Atenei Parmensis, 2004)
The aim of this study was to evaluate the diagnostic role and therapeutic effectiveness of videothoracoscopy in chest trauma. Between 1st January 1993 and 30th September 2003, 112 traumatized patients underwent a videothoracoscopy. The origin of trauma was different : 60 road accidents, 42 accidental falls, 7 knife wounds and 3 firearm wounds. Seventy-six patients presented hemothorax, 21 hemopneumothorax, 10 suspected diaphragmatic injury and 5 pericardium effusion. All patients were hemodynamically stable and conscious. In suspected diaphragmatic rupture patients, videothoracoscopy confirmed the presence of 4 lesions with diameter from 7 to 10cm. The etiopathogenetic causes in the other clinical patterns were: 20 lung lacerations, 17 apical adhesion lacerations, 11 diaphragmatic lesions, 16 wall bleedings and 38 vessel lesions. Ninety patients (80.3%) were treated with video assisted thoracic surgery. The remaining procedures were: 17 drainage tube insertions, 4 thoracotomies and 1 laparotomy. Videothoracoscopy made the use of the primary intention drainage tube obsolete in stable traumatized patients with hemothorax or hemopneumothorax. It is a safe technique that allows the diagnostic and surgical management of the lesions.